2013
DOI: 10.1007/s00586-013-3009-9
|View full text |Cite|
|
Sign up to set email alerts
|

Importance of spinal deformity index in risk evaluation of VCF (vertebral compression fractures) in obese subjects: prospective study

Abstract: Introduction Obesity and osteoporosis share many features and recent studies have identified many similarities suggesting common pathophysiological mechanisms. Obesity is associated with a higher risk of non-traumatic fractures despite bone mineral density (BMD) being normal or even increased. Materials and methods 54 obese subjects were analyzed (51 ± 16 years, 10 males, 44 females). Spinal deformity index (SDI) is a semi-quantitative method that may be a surrogate index of bone microarchitecture. SDI index w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In agreement with previous reports [26], we observed hypovitaminosis D in 72% of SCD patients. Regarding 2009, we had data available for only 12 patients, 5 (41.6%) of which had values compatible with a deficiency condition (<10 ng/mL), while 7 (58.3%) presented levels within the insufficiency range (<30 ng/mL).…”
Section: Biochemical Evaluationssupporting
confidence: 93%
“…In agreement with previous reports [26], we observed hypovitaminosis D in 72% of SCD patients. Regarding 2009, we had data available for only 12 patients, 5 (41.6%) of which had values compatible with a deficiency condition (<10 ng/mL), while 7 (58.3%) presented levels within the insufficiency range (<30 ng/mL).…”
Section: Biochemical Evaluationssupporting
confidence: 93%
“…Subsequently for each subject the SDI was calculated by summing the SQ grade for each of the 13 vertebrae from T4 to L4. In a prospective study on 54 obese subjects (51 ± 16 years, 10 males, 44 females), SDI was found to be an useful index of vertebral fractures risk, as it has been demonstrated in postmenopausal osteoporotic females (10).…”
Section: Obesitymentioning
confidence: 90%
“…DXA essentially focuses on the mineralised component, and it is still the most widely used tool to assess BMD to estimate the bone fragility fracture risk. In a study on obese patients, more than 50% of subjects, with at least one vertebral fracture, exhibited a normal or only slightly reduced BMD, but not osteoporosis, and vertebral fractures occurred 4.4-fold more frequently in patients than controls, thus suggesting that in obese population DXA may not represent an accurate instrument to adequately estimate the fracture risk (10). Data on the risk of hip fractures in obese patients are not conclusive even for the influence of diabetes (11).…”
Section: Obesitymentioning
confidence: 99%
“…(6) However, adipose tissue may have negative effects on bone metabolism. (6) A number of previous studies have shown that fat mass was associated with a decrease of bone mass and bone quality at spine, (7)(8)(9) leading to lower vertebral bone strength. The interaction of the different effects of mechanical loading and adiposity is still unclear.…”
Section: Introductionmentioning
confidence: 99%